Confucian Ethics Exhibited in the Discourse of Chinese Business and Marketing Communication - Zhu, Yunxia (Journal of business ethics, 2009)
With the internationalisation of the Chinese market, Confucian ethics began to draw researchers’ attention. However, little research has been conducted in the specific application of Confucian ethics in marketing communication. This article fills in the research gap by examining how Confucian ethics underpins the discourse of Chinese Expo invitations. Chinese sales managers’ views are incorporated into the analysis as substantiation of findings. Confucian ethics embraces both qing (emotion) and li (reason) and relevant ethical values such as guanxi (connections), qing, and mianzi (face) play an important role for advertising Expos and trade fairs. The study also highlights the complexities of Chinese Expo advertising that is embedded in inviting behaviour. These findings shed light on understanding Confucian ethics in marketing communications in general and have implications for ethical international marketing and advertising practices.